Relationships between Motor Skills and Academic Achievement in School-Aged Children and Adolescents: A Systematic Review - Lijing Wang; Lijuan Wang (MDPI AG, 2024)
Purpose: This review systematically summarizes the studies of the relationship between primary-to-secondary school students' motor skills and academic achievement, and analyzes the relationship between gross and fine motor skills and performance in different subjects. Method: Five electronic databases, Web Of Science, PubMed, PsycINFO, SPORTDiscus, and Academic Search Premier, were searched in March 2023. Semi-quantitative assessment methods were used to analyze the results of the included studies. Results: Seventy-eight articles were included in this systematic review. The semi-quantitative assessment results showed that gross (+, 65.0/62.5%) and fine motor skills (+, 83.3/80%) were positively correlated with overall performance and language performance, with ≥60% of the associations in the same direction. For different subjects, fine motor skills were positively correlated with students' mathematics (+, 75.0%), reading (+, 72.7%), writing (+, 66.7%), and spelling (+, 60.0%) scores. However, the association between gross motor skills and students' mathematics achievement (?, 52.8%), reading (?, 53.8%), and spelling (?, 50.0%) is uncertain, with <60% of the associations in the same direction. Conclusions: It is wise to direct our gaze toward the evolution of motor skills among students, especially primary school students. Different motor skill intervention modes should be selected in a targeted manner according to different subject achievements.